Paraneuronic cells of pseudobranchial neurosecretory system in catfish - Gopesh, A; Yadav, L (Indian Journal of Fisheries, 2011)
The pseudobranchial neurosecretory system is a paracrine system reported in four species of catfish viz. Mystus seenghala, M. aor, M. vittatus and M. cavassius. It is located in the gill region close to the carotid labyrinth. The cells belonging to this system share features with paraneurons and are hypothesized to play role in stress physiology of fishes, especially hypoxia. Present study shows the presence of these cells in the four species of Mystus using specific stains for neurosecretion, viz. acid-violet stain and their probable role in the biology of fishes.